Anatomia do anticristo: narrativa arquetípica no filme de Lars von Trier - Tiezzi, Ricardo (2013)
This work is an analysis of the film Antichrist, by Lars von Trier, from the archetypal criticism proposed by Northrop Frye. The hypothesis is that the film uses narrative patterns whose matrix is biblical to organize his narrative. The first chapter deals with the film and the work of the director. In the second chap-ter, the first step is to define what archetype means in literature, with authors who have worked with the concept. Then our main theory is presented in the work of the Canadian critic Northrop Frye. The third chapter, finally, is an analysis of the film from three different approaches: gender, in which we discuss the tragedy in Anti-christ; mode, in which the narrative of the film is perceived in the tension between the realistic and mythic narratives; and images, in which patterns of imagery stand out from the film in relation to vertical poetic, to the woman and the erotic relation-ship and to the nature and the garden